The Effect of Return of Equity on Company Value with Profitability As A Moderating Variable - Cristofer Sumiok; Farida Aryani; Sari Utami; Frida Magda Sumual; Andrew Patrick Marunduh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is a quantitative research with an explanatory approach, namely an approach that relies on the research objectives of previous research and adds new variations as novelty value to the research being carried out (Abdurahman, 2016). The data used in this study are quantitative data that the researcher obtained from primary sources, namely finance companies listed on the Indonesian stock exchange from 2015 to 2025. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The conclusion in this article show that the Return on Equity variable can have a positive relationship direction and a significant influence on the Company Value variable because the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.011. These results are in line with the research are not in line with the research . In addition, the Profitability variable can also moderate the influence of the Return of Equity variable on the Company Value variable because the same thing the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.000. Thus, it can be concluded that the first and second hypotheses in this article can be accepted and proven.